Current measures of distress may not account for what's most important in existential care interventions: Results of the outlook trial. Issue 6 (December 2020) - Steinhauser, Karen E.; Stechuchak, Karen M.; Ramos, Katherine; Winger, Joseph; Tulsky, James A.; Olsen, Maren K.
Abstract: Objective: Compare the efficacy of two interventions addressing emotional and existential well-being in early life-limiting illness. Method: Primary trial analysis ( n = 135) included patients with advanced cancer, congestive heart failure, or end-stage renal disease; Arm 1 received the Outlook intervention, addressing issues of life completion and preparation, and Arm 2 received relaxation meditation (RM). Primary outcomes at five weeks (primary endpoint) and seven weeks (secondary): completion and preparation (QUAL-E); secondary outcomes: anxiety (POMS) quality of life (FACT-G) and spiritual well-being (FACIT-Sp) subscales of faith, meaning, and peace. Results: Average age was 62; 56% were post-high school-educated, 54% were married, 52% white, 44% female, and 70% had a cancer diagnosis. At baseline, participants demonstrated low levels of anxiety (<5 on POMS subscale) and depression (<10 on CESD) relative to population norms. Results of the primary analysis revealed no significant differences in mean Preparation by treatment arm at five weeks (14.4 Outlook vs. 14.8 RM; between-group difference −0.4 [95% CI, −1.6, 0.8], p = 0.49) or seven weeks (15.2 vs.15.4; between-group difference −0.2 [95% CI, −1.5, 1.0], p = 0.73). There were also no significant differences in mean Life Completion by treatment arm between five weeks (26.6 Outlook vs. 26.3 RM; between-group difference 0.2 [95% CI, −1.2, 1.7], p = 0.76) or seven weeks (26.5 vs. 27.5; between-group difference −1.0 [95% CI, −2.7, 0.7], p = 0.23). Compared to RM, Outlook participants did not have significant differences over time in the secondary outcomes of overall quality of life, anxiety, depression, FACT-G subscales, and FACIT-Sp subscales. Discussion: In early-stage life-limiting illness, Outlook did not demonstrate a significant difference in primary or secondary outcomes relative to RM. Results underscore the importance of pre-screening for distress. Qualitatively, Outlook participants were able to express suppressed emotions, place illness context, reflect on adaptations, and strengthen identity. Screening for distress and identifying specified measures of distress, beyond anxiety and depression, is essential in our ability to adequately assess the multi-dimensional mechanisms that decrease existential suffering.